The story of Jumping Mouse : a native American legend - Steptoe, John, 1950-; Juvenile Collection (Library of Congress) (New York : Lothrop, Lee & Shepard Books, 1984)
The gifts of Magic Frog and his own hopeful and unselfish spirit bring Jumping Mouse finally to the Far-Off Land where no mouse goes hungry.
Keywords: Indians of North America -- Great Plains -- Folklore; Indians of North America -- Great Plains -- Folklore; Mice -- Folklore; Imprints 20th century 1984; Juvenile literature -- New York (N.Y.) -- 1984.